SPEAKING STRATEGIES EMPLOYED BY EXTROVERT AND INTROVERT SPEAKING HIGH ACHIEVERS OF ENGLISH EDUCATION DEPARTMENT, UNISMA - Nur Fazira (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The aims of the research were to investigate speaking strategies used by extrovert and introvert students and to identify the most speaking strategies used by extrovert and introvert students at English Education Department in University of Islam Malang. The research design was descriptive qualitative method. In collecting the data, the researcher used documentation and two types of questionnaire. The participant of this study were the fourth semester students of English Education Study Program at University of Islam Malang who scored "A" in speaking I, II, and III. To analyze the data, the researcher used interpretation of students’ personality and Likert scale. The research findings show that showed that all of high achiever students with extrovert and introvert types use all the same type of strategies, but there is a difference in the most speaking strategies used by extrovert students (affective and metacognitive) and introvert students (cognitive and metacognitive).On the finding of the study, it is addressed to the high achiever students with the extrovert and Introvert type to use all types of strategies, especially affective, cognitive and metacognitive strategies. Then, for teacher are expected to mix several strategies in learning speaking English. And for the future researchers to conduct the same research on a different subject and also can investigate the use of language learning strategies in the other skills.Keywords: Speaking strategy, Extrovert students, Introvert students, High achievers.